Morphometric characteristics of distal airways of guinea pigs sensitized with ovalbumin - Popko, S. S.; Evtushenko, V. M.; Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна (My University, 2020)
The reaction of the structural components of small bronchi and terminal bronchioles is the urgent issue of morphology and medicine in general, as well as one of the insufficiently studied issue in the study of morphological changes in the airways with allergic inflammation in the chronobiological aspect. The purpose of this work is to study the morphometric parameters of distal airways of guinea pigs sensitized with ovalbumin. We have studied the lung of 48 guinea pigs, using histological, morphometric and statistical methods under conditions of experimental ovalbumin-induced allergic inflammation, simulated by three times subcutaneous sensitization and subsequent 8- day intranasal inhalation of ovalbumin. The thickness of mucosa, muscular layer and adventitial layer was determined to assess morphometric parameters of bronchioles and terminal bronchioles. There are reactive changes in morphometric parameters of bronchioles on the 23rd and 30th days of observation, such as the thinning of mucosa and on the 36th day such as muscular-fibrous hyperplasia, accompanied by the narrowing of the bronchioles lumen. There are the most significant confirmed statistically changes in the terminal bronchioles on the 36th day of the experiment such as the thickening of mucosa and adventitial layer, accompanied by muscular hyperplasia and edema of the connective tissue stroma. Thus, sensitization and allergization with ovalbumin of experimental animals cause morpho-functional changes in the structural elements of the wall of bronchioles and terminal bronchioles, which have a staged, mainly multidirectional character and correspond to the main morphological manifestations of allergic inflammation with maximal changes in the late period of its development (the 36th day of the experiment). Актуальною проблемою морфології та медицини в цілому, а також одним із недостатньо досліджених явищ у вивченні морфологічних змін дихальних шляхів при алергічному запаленні в хронобіологічному аспекті залишається реакція структурних компонентів малих бронхів та термінальних бронхіол. Мета роботи - дослідити морфометричні параметри дистальних відділів дихальних шляхів морських свинок, сенсибілізованих овальбуміном. За допомогою гістологічного, морфометричного та статистичного методів вивчили легені 48 самців морської свинки в умовах експериментального овальбумін-індукованого алергічного запалення, яке моделювали шляхом триразової підшкірної сенсибілізації та наступної 8-денної інтраназальної інгаляції овальбуміном. Для дослідження морфометричних показників структурних елементів малих бронхів і термінальних бронхіол визначали товщину їх слизової, м'язової, та адвентиційної оболонок. Встановлено реактивні зміни метричних показників стінки малих бронхів на 23 і 30 доби спостереження у вигляді потоншення слизової оболонки та на 36 добу у вигляді потовщення м'язової пластинки слизової та адвентиційної оболонок, що супроводжувалися зменшенням просвіту бронхів. Найбільш значимі зміни у термінальних бронхіолах, підтверджені статистично, виявлені на 36 добу експерименту у вигляді потовщення слизової та адвентиційної оболонок, що є наслідком гіпертрофії гладеньких міоцитів і набряку сполучнотканинної строми термінальних бронхіол. Таким чином, сенсибілізація та алергізація овальбуміном експериментальних тварин викликають в структурних елементах стінки малих бронхів і термінальних бронхіол морфофункціональні зміни, котрі мають стадійний, переважно різнонаправлений характер і відповідають основним морфологічним проявам алергічного запалення з максимальними змінами протягом пізнього періоду розвитку (36 доба експерименту).
Морфометрична характеристика дистальних відділів дихальних шляхів морських свинок, сенсибілізованих овальбуміном
Keywords: airways; allergic inflammation; ovalbumin; guinea pig; дихальні шляхи; алергічне запалення; овальбумін; морська свинка